(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
Although the new National Civil and Commercial Code does not introduce direct reforms on the Bankruptcy Law, it impacts on the falimentary statute. Thus, minor or referential reforms arise (by referring the Bankruptcy Law to a punctual article of the repealed Civil Code) or others of greater gravitation, such as those regarding to contested subjects, the situation of the new typical contracts and in the patrimonial recomposition actions, expanding its radius of action. Based on this premise, this paper aims to analyze bankruptcy subjects situation, in order to determine whether modifications have taken place on this issue or not.